Unleashing the therapeutic role of cannabidiol in dentistry - Sayem Anwarhussain Mulla; Amit Patil; Sheetal Mali; Ashish K. Jain; Himmat Jaiswal; Hitesh Ramdas Sawant; Ritvi Arvind; Shruti Singh (Journal of Oral Biology and Craniofacial Research)
Cannabidiol (CBD) found in Cannabis sativa is a non-psychoactive compound which is capable of binding to CB1 and CB2 receptors. CBD has recently gained interest in dentistry although it has not been explored sufficiently yet. The therapeutic effects of CBD include anti-inflammatory, analgesic, antioxidant, biological and osteoinductive properties. The aim of this review is to highlight these effects with respect to various oral conditions and shed light on the current limitations and prospects for the use of CBD in maintaining oral health.